2023
DOI: 10.3389/fphar.2022.1074633
|View full text |Cite
|
Sign up to set email alerts
|

Psilocybin sex-dependently reduces alcohol consumption in C57BL/6J mice

Abstract: The classical psychedelic psilocybin is of interest as a treatment for alcohol use disorder (AUD). This study investigated the effects of psilocybin on voluntary ethanol consumption in adult male and female C57BL/6J mice administered saline or psilocybin intraperitoneally as a single dose of 0.1, 0.5, 1.0 or 2.0 mg/kg and provided 20% ethanol utilizing a two-bottle choice alcohol drinking paradigm. Ethanol was provided continuously for 3 days immediately following the administration of psilocybin, then withhel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…The 0.1 mg/kg dose is categorized as a microdose, given that it is one-tenth of the minimum dose required for eliciting behavioral and cellular effects in rats 18,44 . The 1 mg/kg dose is among the most extensively studied doses in rodents for both behavioral and molecular effects [44][45][46] , while 3 mg/kg falls within the range of therapeutic doses for humans 18 . RM-ANOVA analysis revealed no main effect of psilocybin treatment or psilocybin by time interactions for any dose of psilocybin compared to vehicle for either lever presses or infusions (Figure 1G, H).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 0.1 mg/kg dose is categorized as a microdose, given that it is one-tenth of the minimum dose required for eliciting behavioral and cellular effects in rats 18,44 . The 1 mg/kg dose is among the most extensively studied doses in rodents for both behavioral and molecular effects [44][45][46] , while 3 mg/kg falls within the range of therapeutic doses for humans 18 . RM-ANOVA analysis revealed no main effect of psilocybin treatment or psilocybin by time interactions for any dose of psilocybin compared to vehicle for either lever presses or infusions (Figure 1G, H).…”
Section: Resultsmentioning
confidence: 99%
“…Lack of efficacy from the 1.0 mg/kg psilocybin dose on heroin relapse may be due to the fact that occupancy of 5-HT 2A R is estimated to only be ~30% with 1.0 mg/kg IP dosages 62 . The 1 mg/kg dose is among the most extensively studied doses in rodents for both behavioral and molecular effects [44][45][46] , while 3 mg/kg falls within the range of therapeutic doses for humans 18 . While psilocybin does induce head-twitch responses in rodents, the 3 mg/kg dose has been reported to induce less head-twitch responses compared to the 1 mg/kg dose over time but 3 mg/kg induces a rapid, short-lived head-twitch response in rodents that may be further indicative of unique molecular and behavioral consequences that arise from the two doses 39,40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various rodent models of alcohol exposure and consumption have shown sex-specific differences in the amounts of alcohol consumed, aversion resistance, alcohol seeking behaviors, magnitude and direction of alcohol-induced neuronal activity changes, and brain neuronal network adaptations ( Fulenwider et al, 2019 ; Xie et al, 2019 ; Nimitvilai et al, 2020 ; Alper et al, 2022 ; Leyrer-Jackson et al, 2022 ; Foo et al, 2023 ; Nimitvilai-Roberts et al, 2023 ; Sneddon et al, 2023 ). These differences are likely because of distinct neurophysiology and brain connectivity in males versus females.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Shao et al (2021) reported an immediate antidepressant-like effect of acute treatment with psilocybin (1 mg/kg), displayed as a reduced number of failed escapes in the mouse learned-helplessness test. Alper et al (2023) recently demonstrated that psilocybin (0.1–2 mg/kg) reduced alcohol consumption in mice. Single psilocybin injection (0.05–0.1 mg/kg) produced also a pro-motivational effect in the progressive ratio schedule in rats (Higgins et al, 2021).…”
Section: Introductionmentioning
confidence: 99%